Advising Students for Success in Higher Education: An All-Out Effort. (May 2019) - Zhang, Xihui; Gossett, Carol; Simpson, Jill; Davis, Ron
Advising students for success in higher education has always been an important and challenging task. This becomes even more critical nowadays as most higher education institutions are trying to boost their enrollment and improve their retention so that they can be self-sufficient financially and sustainable economically. Research studies on student advising in higher education are abundant. A comprehensive literature review, however, shows that these research studies tend to be myopic in scope and quantitative in methodology. In this research, we attempt to depict a holistic view of an all-out effort on advising students for success, by describing practical approaches and collecting relevant narratives at four levels, including university, college, department, and faculty. It is our hope that this research can help people—whether they are school administrators, faculty members, or college students—have a holistic view of student advising and be successful in their role in higher education.